Gateway placement optimisation problem for mobile multicast design in wireless mesh networks - Sanni, Mistura L.; Hassan Abdalla Hashim, Aisha; Anwar, Farhat; Naji, Ahmed Wathik (2012)
The provision for addressing multiple destinations in group multimedia application delivery over Wireless Mesh Networks (WMN) can be achieved efficiently via multicasting while considering the mobility of Mesh Clients (MC). One of the prominent components of WMN is the Internet Gateway (IGW) which provides wired bridge connection between the backbone network and the Internet. In addition, its cost is significant therefore its placement is one of the main determinants of the overall performance and deployment cost of WMN. This current work explores IGW placement or deployment optimisation for the purpose of incorporation of multicasting and mobility management. Thus, the main focus in this work centres on investigating IGW placement optimisation with the intent of extracting the design issues to answer questions on the appropriateness of the problem formulation and modeling techniques for the optimisation problem. Furthermore, the paper develops the sketch of modeling and formulation of IGW placement problem with the objective of optimising IGW placement while cost of multicast tree and mobility are optimised. This formulation is different from existing works which considers only geographic positioning, load-balancing and interference-based placement. This novel formulation will serve as the basis for IGW placement and selection algorithm to address IGW deployment problem in a mobile multicast WMN architecture.